(untitled) (Journal of Educational Sciences, 2017)
Article considers a creative portrait and problems of formation of musical style of one of the brightest representatives of a genre of a variety song of Shamsha Kaldayakov, the composer, a sign figure of the whole era of Kazakhstan. An embodiment of spirituality and wisdom of the Kazakh people is its traditional culture, namely, song art in which representations about fine and sublime are brightly expressed. Song art of Kazakhs originates in folklore and national creativity. Shamsha’s songs are filled with kindness, warm-heartedness, love. They get at once into soul and the listener’s heart. Still in the Kazakh musicology there is no research of song works of this ingenious composer. Sh. Kaldayakov wrote about 300 songs, and all of them are got by unusually light, pure, spiritualized lyrics. In them he poeticized spiritual life of the simple person – the contemporary. Characteristic quality and feature of song style of the musician is feeling of his melodic intonations thanks to which the composer occupied one of foregrounds among the Kazakh composers – songbooks. His personality is the ideal of upbringing for the modern generation by professional musicians. For Kaldayakov’s music are characteristic the unique intonation filled with a modern melody, freshness of feelings, feeling of mutual return, powerful spiritual and power bond of the composer and listener. Shamsha Kaldayakov – the composer and past and present and future which generalized all intonations of the Kazakh musical culture in the creativity.